Factors influencing patient safety nursing activities among emergency department nurses in Korea: a cross-sectional descriptive study based on the theory of planned behavior - Sojung Park; Jihyun Kim (Journal of Korean Biological Nursing Science, 2026)
Purpose: This study examined associations between the constructs of the Theory of Planned Behavior (TPB) and patient safety nursing activities among emergency department nurses. It also identified factors associated with these activities to provide foundational data for developing strategies to strengthen patient safety nursing practice. Methods: Participants were nurses working in emergency medical centers at seven general hospitals with more than 350 beds in the Daejeon–Chungcheong region. Data were collected from August 12 to August 30, 2024, and analyzed using descriptive statistics, analysis of variance, t-tests, Pearson correlation coefficients, and multiple regression. Results: The mean score for patient safety nursing activities was 4.43 out of 5. The mean TPB construct scores were 6.39 out of 7 for attitude, 6.48 for subjective norm, 5.10 for perceived behavioral control, and 5.65 for behavioral intention. Patient safety nursing activities were positively correlated with attitude (r = .55, p < .001), subjective norm (r = .55, p < .001), perceived behavioral control (r = .59, p < .001), and behavioral intention (r = .65, p < .001). Multiple regression identified behavioral intention (β = .37, p < .001), subjective norm (β = .21, p = .002), attitude (β = .16, p = .017), perceived behavioral control (β = .15, p = .048), and age of 30 to < 35 years (β = .18, p = .010) as significant explanatory factors. The model explained 63% of the variance in patient safety nursing activities (F = 22.21, p < .001). Conclusion: The findings support the applicability of the TPB for explaining patient safety nursing activities among emergency department nurses. Educational interventions and organizational strategies that strengthen behavioral intention, subjective norm, attitude, and perceived behavioral control may help improve patient safety nursing activities and support safer clinical practice.